2008
DOI: 10.1177/0255761407088487
|View full text |Cite
|
Sign up to set email alerts
|

Educating professional musicians: lessons learned from school music

Abstract: Music in Canadian schools at one time focused on skills development. Building on talent, aptitude, prior learning and physical coordination, students would become better at singing or playing an instrument by studying it at school. Over time, new approaches to music teaching and learning opened the umbrella to a more comprehensive range of objectives. Human understanding, social relevance, the ability to work and play together, and many other outcomes are now typically expected of school music programmes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 10 publications
0
4
0
6
Order By: Relevance
“…The curricula in other areas of music include comparatively little, if any, coursework or supervised practical experience related to teaching even though those students often see themselves teaching at some point in the future (Fredrickson, 2007a). Some have suggested that schools teaching primarily music performance skills could benefit by readjusting from a focus on the product to a focus on the process (Carruthers, 2008). In any case, raising awareness and examining ways to adjust current curricula without forcing wholesale change on the existing educational system warrants careful exploration.…”
Section: Discussionmentioning
confidence: 99%
“…The curricula in other areas of music include comparatively little, if any, coursework or supervised practical experience related to teaching even though those students often see themselves teaching at some point in the future (Fredrickson, 2007a). Some have suggested that schools teaching primarily music performance skills could benefit by readjusting from a focus on the product to a focus on the process (Carruthers, 2008). In any case, raising awareness and examining ways to adjust current curricula without forcing wholesale change on the existing educational system warrants careful exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian Gardiner, dkk., (1996), menunjukkan bahwa aktivitas musik sejak dini memiliki pengaruh terhadap meningkatnya nilai tes membaca dan matematika pada anak-anak Taman Kanak Kanak. Menurut Carruthers (2008), pendidikan musik mendukung dan meningkatkan kemampuan belajar dibidang-bidang lain.…”
Section: Pendahuluanunclassified
“…(p. 2) As teachers of music tend to teach in the way they have been taught (Karlsson et al ., 2008) there is a danger that stagnation of learning, teaching and assessment practices can be generationally perpetuated. Curruthers (2008) proposes that university performance programmes still intend a kind of learning that has long been dismissed as limiting, restrictive and ultimately inappropriate for public school curricula. While universities have been slow to catch up with their school colleagues in this regard, Lebler (2007) suggests that a way forward is to consider that ‘teaching practices that have dominated in the past will need to be rethought, and alternatives considered that are likely to produce graduates with the abilities and attributes necessary to adapt readily to a rapidly changing environment’ (p. 206).…”
Section: Assessment In the Ensemble Settingmentioning
confidence: 99%